2010
DOI: 10.2139/ssrn.1815001
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion in the All-Pay Auction: An Experimental Investigation

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…However, as before, there is significant overbidding, both in the benchmark symmetric game and the asymmetric game, with a substantial portion of the overbidding in the latter game being driven by the behavior of the stronger players. Fehr and Schmidt (2011) replicate these findings in an experiment designed to investigate the "exclusion principle" of Baye et al (1993). Finally, Deck and Sheremeta (2012) find support for a discouragement effect in dynamic all-pay auctions with asymmetric players, where theoretical benchmarks (Konrad and Kovenock, 2009) suggest that the discouragement effect might be even stronger than in simultaneous move games.…”
Section: Heterogeneous Playersmentioning
confidence: 76%
See 1 more Smart Citation
“…However, as before, there is significant overbidding, both in the benchmark symmetric game and the asymmetric game, with a substantial portion of the overbidding in the latter game being driven by the behavior of the stronger players. Fehr and Schmidt (2011) replicate these findings in an experiment designed to investigate the "exclusion principle" of Baye et al (1993). Finally, Deck and Sheremeta (2012) find support for a discouragement effect in dynamic all-pay auctions with asymmetric players, where theoretical benchmarks (Konrad and Kovenock, 2009) suggest that the discouragement effect might be even stronger than in simultaneous move games.…”
Section: Heterogeneous Playersmentioning
confidence: 76%
“…Their important finding carries over to symmetric all-pay auctions. Indeed, except for Potters et al (1998), the majority of studies using symmetric all-pay auctions with complete information also find that session averages reflect overbidding (Gneezy and Smorodinsky, 2006;Lugovskyy et al, 2010;Fehr and Schmidt, 2011;Klose and Sheremeta, 2012;Ernst and Thöni, 2013;Ong and Chen, 2013). While Potters et al find evidence of equilibrium play in their two-player all-pay auction experiment, their design imposed an exogenous cap on bids (15% above the prize value), which may have biased behavior toward lower, equilibrium bids.…”
Section: All-pay Auctionsmentioning
confidence: 98%
“…1 See also Noussair and Silver [3] for all-pay auctions with private values and Barut et al [4] for multiple unit all-pay auctions. Fehr and Schmid [5] study exclusion of bidders in all-pay auctions.…”
Section: Open Accessmentioning
confidence: 99%
“…2 Both of these policies aim to reduce 1 Experimental studies found support for the discouragement effect in all-pay auctions (Davis and Reilly, 1998;Deck and Sheremeta, 2012;Fehr and Schmidt, 2015), lottery contests (Fonseca, 2009;Kimbrough et al, 2014), rank-order tournaments (Weigelt et al, 1989;Schotter and Weigelt, 1992), and real-effort tournaments (Cason et al, 2010;Gill and Prowse, 2012). 2 Kaplan and Wettstein (2006) argue that if caps are not rigid, the existence of a cap will not result in increased spending.…”
Section: Introductionmentioning
confidence: 99%